Possibilities of development of air transport infrastructure in Poland - the EU's new financial perspective 2007-2013 - Marciszewska, Elżbieta (Univerzita Pardubice, 2007)
Sources of Funds for the Development of Air Transport Infrastructure in Poland in the EU’s new Financial Perspective 2007-2013 The paper shows the possibilities of financing the development of the air transport infrastructure within the new financial perspectives 2007-2013 of the EU. Investment needs in the air transport sector were shown in the context of market development in Poland. European funds on investments in the air transport sector and related with access to the airports were discussed. Possibilities of using EU funds in private-public partnership were shown, especially on the basis of so called hybrid model of financing an investment in airport and airport-related infrastructure, which consists on simultaneous use of EU funds, private capital and domestic public means.
Zdroje fondů pro rozvoj infrastruktury letecké dopravy v Polsku v EU nový finanční výhled 2007-2013
Keywords: Letecká doprava; Polsko; finanční perspektiva; EU fondy; 2007-2013